Contractor's implied duty to warn design defects - Gan, Gilbert Siang Yang (2015)
In Malaysian construction industry, traditional procurement method is the most common method of procuring a project. In this method, the client contracts with consultants, and has another separate contract with the contractor. Consultants will prepare building designs in accordance to their expertise. Meanwhile contractor will contract with the client to construct the building based on designs given. However, human made mistakes happen, where design defects exist in consultants’ design. Contractor during construction may discover design defects. But sadly, many contractors have a mindset that they are only contracted to construct, and any design defects is not their concern. Some may even intentionally keep silent about the discovery, so that they are able to claim for variation order for when rectification works are required to heal the problem caused by the design defect. Thus, the objective of this study is to identify whether contractor has the implied duty to warn design defects. The research methodology undertaken is by documentary analysis of law cases reported in law journals. The research have identified relevant clauses in the standard forms of contracts, and also eleven law cases related to contractor’s duty to warn design defects. The findings of the analysis are: Contractor owes duty of care to his client. He is expected to warn client of design defect if a reasonably competent contractor would have noticed it and highlight it to his client. Lastly, even if contractor has raised the discovery to his client or contract administrator and was instructed to continue to construct, the contractor will still be liable, as mere discussion of the risk will not release contractor from being responsible. Contractor should take formal and further steps to warn about the perceived dangers and even refusal to carry out the works.